3(q-5)=2(q+5)+3q

Simple and best practice solution for 3(q-5)=2(q+5)+3q equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(q-5)=2(q+5)+3q equation:



3(q-5)=2(q+5)+3q
We move all terms to the left:
3(q-5)-(2(q+5)+3q)=0
We multiply parentheses
3q-(2(q+5)+3q)-15=0
We calculate terms in parentheses: -(2(q+5)+3q), so:
2(q+5)+3q
We add all the numbers together, and all the variables
3q+2(q+5)
We multiply parentheses
3q+2q+10
We add all the numbers together, and all the variables
5q+10
Back to the equation:
-(5q+10)
We get rid of parentheses
3q-5q-10-15=0
We add all the numbers together, and all the variables
-2q-25=0
We move all terms containing q to the left, all other terms to the right
-2q=25
q=25/-2
q=-12+1/2

See similar equations:

| 6(x+4)-4=35 | | 5y=3=-7y=13 | | 15r-5r+3=13 | | 4(4n+2)=-19+7n | | 5u(2u+5)=0 | | −z4=12 | | 18t+2t-6t+3t-16t=13 | | 40=−13(9x+30)+2 | | 4(3-x)+6x=x+10-x | | 4x+7=11x+2 | | 14j-14j+j=10 | | g2+ 5=7 | | 4(3-x)+6x=x+12-x | | 3/2t-4=2/3t-5/6 | | -7w+3w+13w-13w=12 | | 3x-5=2(2x+2) | | 5s+2s-5s-s+s=16 | | 3x+9+9x+3=x | | 8t+2t-7t+3t=18 | | 2/21=h/15 | | 3x+11=7x+19 | | -3k+6=-2(k-4)-(k+2) | | 3(2r-5)=3r-6 | | -7/6k+1=5/3+3/2k | | (x-7)^2=12 | | 9x+7=x-3 | | -7/6k+1=5/3+32k | | 13q-7q-4q=14 | | 110=19x=4 | | n−100-2=0 | | −34=12m | | -4m+4=-3m-6 |

Equations solver categories